ANALISIS KESESUAIAN KUALITAS AIR MINUM TERHADAP DEPOT AIR MINUM ISI ULANG DI KELURAHAN ANDURING BERDASARKAN PERMENKES RI - Hendra Anwar; Rianti Noviza (LPPM Universitas Ekasakti, 2024)
Population growth which is increasing rapidly every year is one of the factors increasing public interest in consuming drinking water from refill drinking water depots (DAMIU). Based on BPS data from the city of Padang, all households in the Kuranji sub-district have used refilled drinking water as a source of drinking water. However, compared to bottled drinking water produced by the industry through an automated process and accompanied by quality testing before being circulated, many DAMIU business managers are not aware of the importance of government policies regarding quality testing of refill drinking water so that a lot of drinking water from DAMIU is declared does not meet drinking water requirements. This study aims to obtain data and information about the quality of drinking water on drinking water DEPOT in Anduring Village which includes physical and chemical parameters of drinking water (pH, Odor, Taste, Color, Turbidity, Total Dissolved Solids (TDS) and Total Hardness as CaCO 3 ) based on PERMENKES RI No. 492/MENKES/PER/IV/2010 . This type of research is classified as laboratory experiment research, to obtain primary data and secondary data. This primary data is obtained from the results of laboratory analysis through samples taken by non- probability sampling with technique convenience sampling while secondary data were obtained from historical reports and published document data which were used as reference and interpretation of the analysis obtained. The results of this study indicate that one of the depots from the three depots as samples in this study was declared not to meet the drinking water quality requirements for one test parameter, namely the pH parameter, while the other two depots were declared to have met the drinking water quality requirements for all tested parameters.